VP109 Identifying Priorities For A National Health Research Funder. (2017) - Turner, Sheila; Ollerhead, Liz; Cook, Andrew
Abstract : INTRODUCTION: It is vitally important that research questions posed are important and that funded research meets a research need or a gap in evidence; these needs may be observed at a local, national or international level. Identifying such research priorities for a national research funder can be challenging, particularly for complex health problems such as health inequalities, where there is a need to consult a large number of experts with a range of expertise. Many methods are used in the identification of such research priorities, however, these can be resource intensive, costly, and logistically challenging particularly where large numbers of people are required and geographical distances are great. METHODS: This study investigated the use of Delphi type survey methods in identifying important research priorities related to health inequalities. Public health professionals with an interest in health inequalities were asked to identify research priorities, these research priorities were subsequently compared to those identified using different methods. RESULTS: Fifty-two public health professionals agreed to take part, the response rates were high, (69 percent, 50 percent and 40 percent) across three survey rounds; which indicated that participants were receptive to the methodology and motivated to respond. The themes identified as encompassing the most important research priorities were: mental health, environmental issues and health behaviours. Within these themes, topic areas which emerged most strongly included: community interventions for prevention of mental health problems, and the food and alcohol environment. CONCLUSIONS: Delphi type survey methods are effective as a means of obtaining opinions from a wide number of relevant experts identifying potential priority topic areas where there is a need for research evidence. Opinions may be sought at local and national levels in order to inform national research priorities.